Peasants in history - Hosbawm, E. J. (ed.) (Bombay, 1980)
In seeking to commemorate Daniel Thorner we have brought to gether a collection of essays by some of his many colleagues, ad mirers and friends. Daniel was in the first instance a student of India, and above all of rural India. It is therefore natural that the largest single group of contributions should deal with the agrarian problems of the subcontinent which was so near to his heart. How ever, Daniel was far from a narrow regional specialist. His strength lay in the capacity for seeing agrarian India as a particular case both of economic development and of peasant agriculture. As Fernand Braudel reminds us, in the last decades of his life he made a world wide impact as an analyst of the peasant economy in general, that is to say, the peasant economy in the context of historical transforma tion and economic development. Hence we chose 'Peasants in History' as the general theme of this commemorative volume. The subjects of papers range widely both in time and place, but the general theme, we trust, provides the cohesion which Daniel would have welcomed. The editors regret the long delay in publication. It will not affect the function of the volume, which is to commemorate a scholar who could not in any case have seen it, but, though mainly due to factors beyond our control, still calls for some apology to the patient contributors. One of them, Erich Jacoby, died in 1979, and we take this opportunity to pay tribute to a distinguished agrarian specialist. We would also like to express our thanks to Anne Destenay who translated Fernand Braudel's portrait of our friend and to Clemens Heller of Maison des Sciences de l'Homme in Paris, which subsidized three other translations. We hope that the eighteen papers collected here will demonstrate how much agrarian and peasant studies and historians of development owe to him. Finally, the editors gratefully acknowledge the assistance rendered to them by Alice Thorner in putting this volume together.
Keywords: Peasantry